Optimal management of the Jucar River and Turia River basins under uncertain drought conditions - Haro Monteagudo, David; Solera, A.; Pedro-Monzonís, M.; Andreu, Joaquín (Elsevier, 2014)
This paper presents a methodology to assess the best behavior achievable for a water resources system, and we apply it to the joint system of the Jucar River and Turia River basins in Spain. The resources of the two rivers are used jointly to meet the different water uses within the region, especially urban demands and environmental requirements. The climate change effects in this area are predicted to be particularly severe in this area with great variability in drought patterns. The results are particularly suitable for evaluating the best performance of the system under uncertain conditions.
Keywords: Optimization; risk assessment; drought; water resources planning and management; AQUATOOL